Differential stimulation of murine resident peritoneal cells by selectively opsonized encapsulated and acapsular Cryptococcus neoformans. - Levitz, S M (1988)
Stimulation of murine resident peritoneal cells (RPCs) by encapsulated strain 52 and acapsular strain 602 of Cryptococcus neoformans was compared. Fresh serum was required for fungistasis of both strains. Encapsulated organisms were killed only if the RPCs were activated with gamma interferon (IFN-gamma) or if the organisms were opsonized with anticapsular immunoglobulin G (IgG). In contrast, acapsular organisms were killed by unactivated RPCs, with enhanced killing seen if the cells were activated with IFN-gamma. Except for unopsonized strain 52, all organisms of both strains were phagocytosed. The respiratory burst was stimulated in unactivated and IFN-gamma-activated RPCs by encapsulated strain 52 only if organisms were opsonized with both IgG and serum. In contrast, the burst was stimulated by acapsular strain 602, with or without opsonization. Only unopsonized strain 602 stimulated significant lysosomal enzyme release. Nitrite synthesis by unactivated RPCs was seen only if strain 52 was opsonized with anticapsular IgG or if strain 602 was opsonized with serum. If RPCs were activated with IFN-gamma, then serum-opsonized strain 52 was also able to stimulate nitrite synthesis. Thus, RPC killing, phagocytosis, respiratory burst, lysosomal enzyme release, and nitrite synthesis following challenge by both unopsonized and opsonized with serum or anticapsular IgG strains 52 and 602 varied according to the surface properties of the organisms, the state of activation of the RPCs, and the particular RPC event studied. However, stimulation of nitrite synthesis was the only RPC event which correlated with killing of both strains.